2012
DOI: 10.3109/14767058.2012.666587
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus and Epstein–Barr virus may be associated with some cases of cerebral palsy

Abstract: Evidence of congenital viral infection was uncommon in cases of cerebral palsy and controls. However, CMV and EBV were significantly associated with cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…The proportion of CP cases attributed to cCMV in this study was 1.5%. This is comparable to a state-based Australian study that retrospectively analyzed newborn screening cards 15 and estimates of severe neurological impairment from a recent European long-term follow up study. 10 This study utilized data available in an Australian CP register where cCMV was reported as the known cause and a requirement of laboratory confirmed evidence of CMV infection.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The proportion of CP cases attributed to cCMV in this study was 1.5%. This is comparable to a state-based Australian study that retrospectively analyzed newborn screening cards 15 and estimates of severe neurological impairment from a recent European long-term follow up study. 10 This study utilized data available in an Australian CP register where cCMV was reported as the known cause and a requirement of laboratory confirmed evidence of CMV infection.…”
Section: Discussionsupporting
confidence: 73%
“…An Australian case-control study 14,15 identified cCMV DNA in 1.5% of newborn screening cards from CP cases in a revised estimate. 15 Clinical details of the children with CP and cCMV were not reported. Radiographic features [16][17][18] and/or neonatal 19 or early childhood signs 17,18 have also been described in a small case series of children with CP and confirmed cCMV, however the CP profile of these children was not well defined.…”
mentioning
confidence: 99%
“…The increased prevalence of placental and cord abnormalities in children subsequently diagnosed with cerebral palsy underlines the importance of requesting placental histology and cord arterial gases in all caseswhere the baby is delivered in poor condition13 . spots from cerebral palsy cases and controls show increased cerebral palsy risk after both Cytomegalovirus and Epstein Barr virus infections during pregnancy40 .…”
mentioning
confidence: 99%
“…Permanent physical sequelae include microcephaly, hearing loss, vision loss, and mental retardation. Furthermore, there is evidence that intrauterine CMV infection is significantly associated with cerebral palsy [11 ]. Between 20,000 and 40,000 children are born with congenital CMV infections in the USA each year, resulting in 100–200 deaths and 4,000–8,000 individuals developing permanent neurological sequelae [12, 13].…”
Section: Overt Danger: CMV Infection and Its Burden To Public Healthmentioning
confidence: 99%